Formation of a SMC Structure Upon Warm Isothermal Deformation and its Influence on Martensitic Transformations in Titanium–Nickelide Based Alloys - Lotkov A. I. Aleksandr Ivanovich; Grishkov V. N. Viktor Nikolaevich; Kashin O. A. Oleg Aleksandrovich; Baturin A. A. Anatoly Anatolievich; Timkin V. N. Viktor Nikolaevich; Zhapova D. Yu. Dorzhima Yurjevna (2015, 2015)
Title screen